Concrete Modular Pavements – Types, Issues And Challenges - Audrius Vaitkus; Judita Gražulytė; Rita Kleizienė; Viktoras Vorobjovas; Ovidijus Šernas (The Baltic Journal of Road and Bridge Engineering)
According to the European Asphalt Pavement Association, more than 90 per cent of the European road network is paved with asphalt. Constantly increasing traffic volume and climate change accelerate deterioration of current pavements. As a result, there arises a need to rehabilitate them prematurely. Repair and rehabilitation work lead to traffic congestion, which is one of the most significant concerns in highly trafficked roads and urban streets. Concrete modular pavements consisting of precast concrete slabs are a reasonable solution to deal with the road works since their construction, as well as repair, is time-saving. Repair works typically are implemented during a low traffic period (usually at night). A primary purpose of concrete modular pavements is heavily trafficked roads and other transport areas. This paper focuses on concrete modular pavements, their types, issues and challenges related to their design, slab fabrication and pavement construction. The conducted analysis revealed 15 different types of concrete modular pavements that differ from the techniques of slab joints and load transfer between the adjacent slabs. More than 20 issues and challenges related to the design of modular elements, slab fabrication and pavement construction were identified. Finally, the existing practice of concrete modular pavements was summarised and the gaps of scientific knowledge, as well as a need for comprehensive research, were defined.